2007
DOI: 10.1152/ajpcell.00394.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple repressor pathways contribute to phenotypic switching of vascular smooth muscle cells

Abstract: Kawai-Kowase K, Owens GK. Multiple repressor pathways contribute to phenotypic switching of vascular smooth muscle cells. Am J Physiol Cell Physiol 292: C59 -C69, 2007. First published September 6, 2006; doi:10.1152/ajpcell.00394.2006.-Smooth muscle cell (SMC) differentiation is an essential component of vascular development and these cells perform biosynthetic, proliferative, and contractile roles in the vessel wall. SMCs are not terminally differentiated and possess the ability to modulate their phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
231
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(240 citation statements)
references
References 113 publications
9
231
0
Order By: Relevance
“…Previous studies have demonstrated ERK1/2 is an important upstream regulator of VSMC phenotypic switch 20. Thus, we sought to determine if VPO1/HOCl promotes H 2 O 2 ‐induced VSMC phenotypic switch by activating ERK1/2.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have demonstrated ERK1/2 is an important upstream regulator of VSMC phenotypic switch 20. Thus, we sought to determine if VPO1/HOCl promotes H 2 O 2 ‐induced VSMC phenotypic switch by activating ERK1/2.…”
Section: Resultsmentioning
confidence: 97%
“…The contractile phenotype of VSMCs is characterized by a low rate of cell proliferation and migration and high expression of contractile proteins such as α‐SMA, SM22 (transgelin), and smooth muscle myosin heavy chain 11 (MYH11) 24, 54, 55, 56, 57. The synthetic phenotype is characterized by a high rate of cell proliferation and migration and decreased expression of contractile proteins 24, 54, 55, 56, 57.…”
Section: Resultsmentioning
confidence: 99%
“…The contractile phenotype of VSMCs is characterized by a low rate of cell proliferation and migration and high expression of contractile proteins such as α‐SMA, SM22 (transgelin), and smooth muscle myosin heavy chain 11 (MYH11) 24, 54, 55, 56, 57. The synthetic phenotype is characterized by a high rate of cell proliferation and migration and decreased expression of contractile proteins 24, 54, 55, 56, 57. Disruption of the balance of the VSMCs phenotypes (for example, a transition from a contractile phenotype to a synthetic phenotype) will favor VSMCs proliferation and migration, leading to development of neointimal formation and restenosis after vascular injury 24, 55, 56, 57, 58.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During surgical revascularization, the integrity of the endothelium may be damaged by mechanical injuries and result in the infiltration of inflammatory cells. Both dysfunctional endothelial cells and inflammatory cells synthesize and secrete various cytokines and growth factors, especially platelet‐derived growth factor (PDGF), which facilitates the switch of VSMCs from a contractile phenotype to a synthetic phenotype 5. Subsequently, the synthetic VSMCs, which express decreased levels of adult smooth muscle–specific proteins, migrate from the media into the intimal layer and proliferate to form neointimal lesions 6.…”
Section: Introductionmentioning
confidence: 99%